Performance analysis of voip network between KK3 & KK5 Universiti Malaysia Pahang using opnet simulator - Choo, Xin Ying (2014)
Voice over Internet Protocol (V0IP) is rapidly growing and the market is booming because of its economical benefits and innovative phone services. This research is done by simulating the current network topology of KK3 to KK5 Universiti Malaysia Pahang in OPNET Modeler 14.5 to generate the results to be analyzed. The main objective of this research is to determine how many concurrent VoIP users can the current network between KK3 and KK5 supported at the same time. Besides that, how many VoIP users can be supported when HTTP traffic and video streaming is added in the network. The simulation results will be analyzed in this research is jitter, packet end-to-end delay, and MOS. In the simulation, two scenarios will be created which is scenario with only VoIP traffic and scenario with busy traffic which is HTTP and Video streaming traffic. The number of concurrent VoIP users started from 100 users and added 50 users each time in both scenarios until the value reached the threshold. The simulation result had shown the maximum concurrent VoIP user for scenario with only VolP traffic is 250 users. On the other hand, the maximum number of concurrent VoIP user for scenario with HTTP and Video Streaming traffic is 100 users.